Substitutional potential of mephedrone: an analysis of the subjective effects. (23rd July 2013) - Kapitány‐Fövény, Máté; Kertész, Máté; Winstock, Adam; Deluca, Paolo; Corazza, Ornella; Farkas, Judit; Zacher, Gábor; Urbán, Róbert; Demetrovics, Zsolt
Abstract : Objective: In the past 25–30 years, a large number of synthetic and non‐synthetic drugs have appeared on the recreational scene, but with the exception of 4‐methylmethcathinone (mephedrone), none of these substances reached the popularity of ecstasy [3, 4‐methylenedioxy‐N‐methylamphetamine, (MDMA)]. Authors aimed to determine the subjective effects of mephedrone in order to understand how mephedrone can serve as a potential substitute for entactogens, such as MDMA. Methods: One hundred forty‐five mephedrone users—recruited by snowball method—filled out a questionnaire on their patterns of use and experienced subjective effects of mephedrone. Results: Factor analysis revealed six factors of mephedrone‐induced subjective effects: positive emotions, sensibility, adverse somatic effects, adverse psychological effects, stimulant effects, and psychedelic effects. A preference list of subjective effects indicates that mephedrone is popular primarily for its psychostimulant and entactogen effects. Latent class analysis identified two classes of mephedrone users, with closely parallel profiles. The two classes differed in severity of subjective experience in a way that was consistent across the six dimensions. Conclusions: By having similar subjective effects as MDMA and other entactogens, mephedrone seems able to substitute other enactogenic stimulants. Copyright © 2013 John Wiley & Sons, Ltd.